Remarks on the thickness of Ksub{n, n, n} - Yang, Yan (Ars mathematica contemporanea, 2017)
The thickness ?$θ(G)$? of a graph ?$G$? is the minimum number of planar subgraphs into which ?$G$? can be decomposed. In this paper, we provide a new upper bound for the thickness of the complete tripartite graphs ?$K_{n, n, n} \; (n \ge 3)$? and obtain ?$θ(K_{n, n, n}) = \lceil \frac{n+1}{3}\rceil$?, when ?$n \equiv 3 \pmod{6}$?.
Keywords: debelina; grafi; polni tridelni graf